2014
DOI: 10.1080/01490451.2014.918214
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Deep-Sea Sediments from Afanasy Nikitin Seamount, Equatorial Indian Ocean

Abstract: Deep-sea sediments can reveal much about the last 200 million years of Earth history, including the history of ocean life and climate. Microbial diversity in Afanasy Nikitin seamount located at Equatorial East Indian Ocean (EEIO) was investigated. Deep sea sediment collected at 150 cm depth (»67 ky BP) exhibited a dominance of clones clustering in the phylum Firmicutes (63%), followed by g-Proteobacteria (37%). The bacterial diversity within sediment at 200 cm depth (»84 ky BP) was dominated by g-Proteobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Larger polymers and organic particles were accumulated at the bottom of DCM layer or deeper, which provided feasible food sources for Bacteroidetes at 150 m. Bacteroidetes are well-known particle-associated microorganisms (Kabisch et al, 2014) and their roles as degraders in oligotrophic marine environment have been well confirmed by recent genome sequencing information (Fernández-Gómez et al, 2013;Kabisch et al, 2014). Obviously, phytoplankton along with other biogeochemical parameters, such as nutrients (Fuhrman and Steele, 2008) played vital roles affecting microbial community structure, as discussed in studies on bacterial diversity in different locations of the Indian Ocean sediment (Wu et al, 2011;Khandeparker et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Larger polymers and organic particles were accumulated at the bottom of DCM layer or deeper, which provided feasible food sources for Bacteroidetes at 150 m. Bacteroidetes are well-known particle-associated microorganisms (Kabisch et al, 2014) and their roles as degraders in oligotrophic marine environment have been well confirmed by recent genome sequencing information (Fernández-Gómez et al, 2013;Kabisch et al, 2014). Obviously, phytoplankton along with other biogeochemical parameters, such as nutrients (Fuhrman and Steele, 2008) played vital roles affecting microbial community structure, as discussed in studies on bacterial diversity in different locations of the Indian Ocean sediment (Wu et al, 2011;Khandeparker et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Johnson et al (1968) explored the composition of bacteria in the Indian Ocean by isolation of the cultivable species, and additional isolation-based studies followed (Nair et al, 1994;Bharathi and Nair, 2005). More recently, sediment bacterial distribution in the central margin and two sediment cores in the equator region of the Indian Ocean were investigated (Hoek et al, 2003;Khandeparker et al, 2014). In order to explore the vital roles that microbes may play, further characterization of the composition and distribution of microorganisms in the Indian Ocean is needed.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have shown that Gammaproteobacteria were abundant in sediments surrounding ferromanganese crusts at the Takuyo-Daigo seamount, while Alphaproteobacteria and Gammaproteobacteria were dominant in sand samples from a hydrothermal field at the Suiyo seamount 9 , 10 . Moreover, at 150 cm depth sediments collected from Afanasy Nikitin seamount were dominated by clones belonging to the Firmicutes and Gammaproteobacteria, while Gammaproteobacteria and Betaproteobacteria were dominant in sediments at 200 cm depth 11 . In this study, we performed a systematic investigation of the bacterial diversity and community structure in sediments collected from 14 stations on a seamount located in the tropical western Pacific Ocean; additionally, this cruise marks the first time this seamount has been surveyed.…”
Section: Introductionmentioning
confidence: 96%
“…It has been hypothesized that seamounts support high levels of biodiversity and endemism of marine animals 4 . Characterization of microbial populations in sediments has been undertaken for the Marsili and Palinuro seamounts in the Tyrrhenian Sea 5 8 ; the Takuyo-Daigo seamount in the northwest Pacific Ocean 9 ; the Suiyo seamount in the western Pacific Ocean 10 ; and the Afanasy Nikitin seamount, which is located in the equatorial East Indian Ocean 11 . Bacterial abundance and biomass were significantly higher in sediments of the Marsili and Palinuro seamounts than in non-seamount sediments 5 .…”
Section: Introductionmentioning
confidence: 99%
“…One characteristic feature of the North Indian Ocean is the marked Oxygen Minimum Zone (OMZ) layered in the subsurface of the upwelling regions (Roullier et al, 2014). Even though there have been studies of the bacterial community composition of the Indian Ocean seawater (Sunagawa et al, 2015; Wang et al, 2016) and deep-sea sediments (Wu et al, 2011; Khandeparker et al, 2014), the diversity and genomics of the Bacteroidetes populations remain poorly characterized in this area. This is then a good opportunity to analyze whether micro-diversity exists in a particular Bacteroidetes taxon dominating after the phytoplankton bloom event.…”
Section: Introductionmentioning
confidence: 99%